2002
DOI: 10.1002/pen.11112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the processing conditions on a two‐phase reactive blend system: EVA/PP thermoplastic vulcanizate

Abstract: The elaboration of a TPV based on copolymer of ethylene and vinyl acetate (EVA) and polypropylene (PP) as thermoplastic phase was investigated in a batch mixer. The crosslinking reaction is carried out through a transesterification reaction between ester groups of EVA and alcoxysilane groups of the crosslinker agent tetrapropoxyorthosilicate (TPOS). The main advantage of this crosslinking reaction is that it can be well controlled and suitable for different processing conditions. The aim of the present study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 14 publications
6
31
0
Order By: Relevance
“…For both the systems we observed that torque attains a maximum in the early stages of mixing and subsequently decreases to a rather stationary value, when also the melt temperature becomes quite constant. Similar trends were reported for melt blending processes of others thermoplastic polymers and fillers, indicating the achievement of uniform dispersions between polymers and HA particles [20,22].…”
Section: Biomaterials Preparation and Characterizationsupporting
confidence: 81%
“…For both the systems we observed that torque attains a maximum in the early stages of mixing and subsequently decreases to a rather stationary value, when also the melt temperature becomes quite constant. Similar trends were reported for melt blending processes of others thermoplastic polymers and fillers, indicating the achievement of uniform dispersions between polymers and HA particles [20,22].…”
Section: Biomaterials Preparation and Characterizationsupporting
confidence: 81%
“…As a result, the stress transferred by the low viscosity thermoplastic phase becomes less and less effective in deforming the elastomeric domains and coalescence of the elastomeric domains becomes more and more hindered due to increased viscosity and elasticity of this phase. Consequently, the cross-linking reaction merely stabilizes the already existing, rather coarse dispersed morphology of the elastomeric domains, without any further morphological refinement [60][61][62]. With this in mind, although the co-continuity is a crucial factor in this process, a stable and unchangeable co-continuous morphology in the intermediate stage of dynamic vulcanization is not a desirable situation.…”
Section: Morphology Development In Dynamically Vulcanized Nonplasticimentioning
confidence: 99%
“…The fact that high and low viscosity ratio systems represent completely different initial morphological states prior to dynamic vulcanization means that the torque requirement for mixing could be substantially different from one system to another. Indeed, blends with high initial viscosity ratio with a dispersed thermoplastic phase in an elastomeric matrix have demonstrated a shoulder in the mixing torque during dynamic vulcanization process [61]. This shoulder appears while the blend structure passes through a co-continuous morphology prior to complete vulcanization and dispersion of the elastomeric component in the thermoplastic phase.…”
Section: Morphology Development In Dynamically Vulcanized Nonplasticimentioning
confidence: 99%
See 2 more Smart Citations